Pelatihan Pembuatan Pelet Terapung Dengan Kadar Protein 30% Berbasis Bahan Baku Lokal, Dengan Menggunakan Metode Pearson Square di Desa Tugalagawu, Kecamatan Sirombu, Nias Barat - Asokhiwa Zega; Adesk Kristiani Zebua; Beriman Gulo; Dumasari Telaumbanua; Dara Dwista Telaumbanua; Fakta Perjuangan Lombu; Januari Dawolo (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service activity was carried out in Tugalagawu Village, Sirombu District, West Nias Regency, in response to the low technical capacity of fish farming groups and vocational school students in independently producing fish feed. Through a collaborative participatory approach, the activity aimed to enhance participants' understanding and skills in designing and producing 30% protein-based floating fish feed using local raw materials, employing the Pearson Square method. The implementation began on April 17, 2025, concurrently with the internship program for University of Nias students, and involved technical department officials, village government representatives, vocational education institutions, and the fish farming community. The activity includes lectures, discussions, and hands-on practice, from ingredient formulation, mixing, molding, to drying the feed. The results show a significant improvement in participants' technical understanding and practical skills, as well as the creation of high-quality feed products tested directly in the field. In addition to producing modules, tutorial videos, and local working units, the activity also contributed to enhanced economic self-reliance and strengthened village institutional networks. These findings underscore that capacity-building through science and technology-based community service can drive productive and sustainable transformation in the village fisheries sector.